Funciones Ejecutivas en Tres Personas Jóvenes entre los 15 y 31 años con Depresión e Intento de Suicidio de la Ciudad de Bogotá: Serie de Casos - Alfonso Gámez, Daniela Patricia (Universidad Antonio Nariño, 2022)
The objective of this research was to describe the relationship between executive deficit, depression and attempted suicide in young people in the city of Bogotá, due to the increase in the trend of suicide mortality in Colombia in adolescent and young age groups, and thus , contribute to the range of explanations of the phenomenon from Neuroscience and Executive Functions regarding the possible existence of an executive dysfunction that predisposes individuals with certain environmental and psychological vulnerabilities, to the development of episodes or affective disorders such as depression that is related to subsequent onset of suicidal thoughts and behaviours. The study is developed under the methodology of a series of quantitative cases of descriptive scope